A Nutrient Formulation Affects Developmental Myelination in Term Infants: A Randomized Clinical Trial - Schneider, Nora; Bruchhage, Muriel M. K.; O'Neill, Barry V.; Hartweg, Mickaël; Tanguy, Jérôme; Steiner, Pascal; Mutungi, Gisella; O'Regan, Jonathan; Mcsweeney, Séamus; D'Sa, Viren; Deoni, Sean C. L. (Frontiers in Nutrition, 2022)
Background and Objectives: Observational studies suggest differences between breast-fed and formula-fed infants in developmental myelination, a key brain process for learning. The study aims at investigating the efficacy of a blend of docosahexaenoic acid, arachidonic acid, iron, vitamin B12, folic acid, and sphingomyelin from a uniquely processed whey protein concentrate enriched in alpha-lactalbumin and phospholipids compared to a control formulation on myelination, cognitive and behavioral development in the first 6 months of life. Methods: These are six-month results from an ongoing two-center, randomized controlled trial with a 12-month intervention period (completed for all participants). N = 81 full term, neurotypical infants of both sexes were randomized into investigational (N = 42) or control group (N = 39). N = 108 non-randomized breast-fed children serve as a natural reference group. Main outcomes are myelination (MRI), cognitive (Bayley-III), social-emotional development (ASQ:SE-2), sleep (BISQ), and safety (growth, adverse events). Results: The full analyses set comprises N = 66 infants. Significant differences in myelin structure, volume and rate of myelination were observed in favor of the investigational myelin blend at 3 and 6 months of life. Effects were demonstrated for whole brain myelin and for cerebellar, parietal, occipital, and temporal regions, known to be functionally involved in sensory, motor and language skills. No statistically significant differences were found for early behavior and cognition scores. Conclusions: This is the first study demonstrating efficacy of a myelin nutrient blend in well-nourished, term infants on developmental myelination, which may be foundational for later cognitive and learning outcomes.